Apolipoprotein E3 and E4 isoforms exhibit differing effects in countering endotoxins - Puthia, Manoj; Marzinek, Jan K; Vesela, Katerina; Larsson, Axel; Schmidtchen, Artur; Bond, Peter J; Petrlova, Jitka (The Journal of biological chemistry, 2025)
Apolipoprotein E (APOE) is distributed across various human tissues and plays a crucial role in lipid metabolism. Recent investigations have uncovered an additional facet of APOE's functionality, revealing its role in host defense against bacterial infections. To assess the antibacterial attributes of APOE3 and APOE4, we conducted antibacterial assays using Pseudomonas aeruginosa and Escherichia coli. Exploring the interaction between APOE isoforms and lipopolysaccharides (LPSs) from E. coli, we conducted several experiments, including gel shift assays, CD, and fluorescence spectroscopy. Furthermore, the interaction between APOE isoforms and LPS was further substantiated through atomic resolution molecular dynamics simulations. The presence of LPS induced the aggregation of APOE isoforms, a phenomenon confirmed through specific amyloid staining, as well as fluorescence and electron microscopy. The scavenging effects of APOE3/4 isoforms were studied through both in vitro and in vivo experiments. In summary, our study established that APOE isoforms exhibit binding to LPS, with a more pronounced affinity and complex formation observed for APOE4 compared with APOE3. Furthermore, our data suggest that APOE isoforms neutralize LPS through aggregation, leading to a reduction of local inflammation in experimental animal models. In addition, both isoforms demonstrated inhibitory effects on the growth of P. aeruginosa and E. coli. These findings provide new insights into the multifunctionality of APOE in the human body, particularly its role in innate immunity during bacterial infections.
Keywords: apolipoprotein E isoforms; Protein Isoforms; antimicrobial peptides; simulace molekulární dynamiky; Lipopolysaccharides; Apolipoprotein E3; endotoxin; lipopolysacharidy; Apolipoprotein E4; Molecular Dynamics Simulation; Escherichia coli; protein - isoformy; Animals; lidé; Pseudomonas aeruginosa; Humans; zvířata; myši; apolipoprotein E4; protein aggregation; apolipoprotein E3; host defense; Mice